Semiconductor-Based Sensors and their Wide Applications (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Semiconductor-based sensors are one of the key components of modern technological advancement, and their application in various industrial sectors is expanding. These sensors hold significant importance and are widely used in fields such as medicine, automotive engineering, and environmental monitoring. They enable the rapid and reliable collection of accurate data in various conditions, which plays a crucial role in the decision-making process.